The Structure of Associative Fields of Stimuli Природа / Природа / Прырода / Die Natur in East Slavic and German Languages - Terekhova, Diana (Lesya Ukrainka Eastern European National University, 2017)
Association test is one of the traditional methods of studying the images of linguistic consciousness that hide behind a word in a particular culture. A number of associative experiments have been carried out in the early twentieth century in Ukraine, Russia, Belarus, and Germany. Students of higher education institutions of these countries (100 representatives from each nation) were the respondents of the experiment. The materials of the free word associatin test are used in the article. The article deals with psycholinguistic analyses of associative fields of the stimuli ПРИРОДА / ПРИРОДА / ПРЫРОДА / DIE NATUR demonstrating features of corresponding fragments of the mental and lingual worldviews of the Ukrainians, Russians, and Belarusians. The structure and composition of the associative fields is analyzed with the help of the “associative gestalt”. The gestalt structure of associative fields in each language clearly demostrate the differences in images of linguistic consciousness. The differences are seen in the different number of zones in four gestalts of studied languages, in the presence of some zones only in certain gestalt unlike others, in size of zones, that define their rating and originality of structure of each associative field, in quantitative and qualitative composition of zones as well as in the cores of gestalts. Традиційним методом дослідження образів мовної свідомості, що стоять за словом у певній культурі, є асоціативний експеримент. У дослідженні проведено низку асоціативних експериментів на початку ХХІ століття в Україні, Росії, Білорусі та Німеччині. Респондентами були студенти вищих навчальних закладів цих країн (по сто представників від кожного народу). У роботі використано матеріали вільного асоціативного експерименту. У статті репрезентовано результати психолінгвістичного аналізу асоціативних полів слів-стимулів ПРИРОДА / ПРИРОДА / ПРЫРОДА / DIE NATUR, виявлено загальні риси та етнокультурну специфіку відповідних фрагментів образів світу українців, росіян, білорусів та німців. Структуру і склад асоціативних полів проаналізовано за допомогою "асоціативного гештальту", у наслідок чого визначено різноманітні зони, які наочно демонструють своєрідність асоціативних полів у кожній мові. Розбіжності виявлено в кількості зон у гештальтах, у наявності окремих зон лише в певному гештальті на відміну від інших, у різному обсязі зон, що визначає їхній рейтинг та неповторність будови кожного асоціативного поля, у кількісному та якісному складі зон, а також у ядрах гештальтів.
Keywords: world image; linguistic consciousness; association test; association; associative field; associative gestalt; образ світу; мовна свідомість; асоціативний експеримент; асоціація; асоціативне поле; асоціативний гештальт